Adolescents' Use of Digital Technologies and Preferences for Mobile Health Coaching in Public Mental Health Settings - Kelly A. Aschbrenner; Kelly A. Aschbrenner; John A. Naslund; Elizabeth F. Tomlinson; Allison Kinney; Sarah I. Pratt; Sarah I. Pratt; Mary F. Brunette; Mary F. Brunette (Frontiers Media S.A., 2019)
Objective: Youth with mental illnesses often engage in unhealthy behaviors associated with early mortality from physical diseases in adulthood, but interventions to support positive health behaviors are rarely offered as part of routine mental health care for this group. Digital health technology that is desirable, accessible, and affordable has the potential to address health behaviors in public mental health settings where many adolescents with severe mental health problems receive care. The aims of this study were to examine how adolescents receiving public mental health services use digital technology and social media and to explore their preferences using technology to support health and wellness.Methods: Using a convergent parallel mixed methods design, we surveyed adolescents ages 13-18 from four community mental health centers in one state and conducted focus group interviews to explore their perspectives on using digital technology and social media to receive health coaching and connect with peers to support healthy behaviors. The survey and focus group data were merged to inform the future development of a digital health intervention for adolescents receiving public mental health services.Results: Of 121 survey respondents (mean age 15.2, SD = 1.5), 92% had a cell phone, 79% had a smartphone, 90% used text messaging, and 98% used social media. Focus group interviews revealed that adolescents were interested in receiving strengths-based mobile health coaching, and they preferred structured online peer-to-peer interactions in which a professional moderator promotes positive connections and adherence to privacy guidelines.Conclusions: Adolescents receiving public mental health services in this study had access to smartphones and were frequent social media users. These data suggest that digital health interventions to promote health and wellness among adolescents may be scalable in community mental health settings. Adolescent participants suggested that digital health interventions for this group should focus on strengths and online peer support for health promotion should include a professional moderator to foster and manage peer-to-peer interactions.